Familial amyloidosis cutis dyschromica in three siblings: report from Indonesia - Melyawati Hermawan; Rahadi Rihatmadja; Sondang Pandjaitan Sirait (PAGEPress Publications, 2014)
Amyloidosis cutis dyschromica (ACD) is an extremely rare type of primary cutaneous amyloidosis. To date there are fewer than 40 published cases worldwide; some were reported affecting several family members. Its resemblance to other common pigmentation disorders makes it rarely recognized at first sight. Our patient, the 12-year-old firstborn son of non-consanguineous parents presented with generalized mottled pigmentation starting from lower extremities. His siblings suffered from similar condition. The clue for diagnosis is the amyloid deposition in the papillary dermis. The etiology of ACD is still unknown, but genetic factors and ultraviolet radiation are implicated. It is proposed that disturbance of keratinocyte repair following ultraviolet radiation results in amyloid deposition. The treatment remains a challenge. Oral acitretin treatment, thought to repair keratinization defect, gave a slight improvement in our case. Our is the first case of ACD reported in Indonesia.